Two Austro-Hungarian Women Writers, Anna Tutsek and Terka Lux, Creating New Urban Identities in Early Twentieth-Century Budapest - Kádár Judit (HUNGARIAN CULTURAL STUDIES: E-JOURNAL OF THE AMERICAN HUNGARIAN EDUCATORS ASSOCIATION, 2015)
In this paper, I examine some literary texts of two turn-of- the century Hungarian women writers, Anna Tutsek and Terka Lux who left behind their childhood environment in remote regions of the Austro-Hungarian Monarchy in order to move to Budapest, the capital of the eastern part of the Empire. Assuming that individuals hold multiple identities that are flexible and inevitably affected by environmental and social changes, my main focus is on the transformation of their ethnic, regional, occupational and gender identity influenced by the disengagement from their birthplace. Within a context of Hungarian−Eastern-European women's social history, I investigate how migration had led them to reshape their original identities and create new ones and how these emigrant writers reacted to the loss of cultural and social norms in which they had previously lived.